Psychosocial services provided by licensed cardiac rehabilitation programs - Bush, Montika; Evenson, Kelly R.; Aylward, Aileen; Cyr, Julianne M.; Kucharska-Newton, Anna (Frontiers in Rehabilitation Sciences, 2023)
Background Professional health organizations recommend that outpatient cardiac rehabilitation programs include activities to optimize the physical, mental, and social well-being of patients. The study objectives were to describe among cardiac rehabilitation programs (1) mental health assessments performed; (2) psychosocial services offered; and (3) leadership's perception of barriers to psychosocial services offerings. Methods A cross-sectional survey of North Carolina licensed outpatient cardiac rehabilitation programs on their 2018 services was conducted. Descriptive statistics were used to summarize survey responses. Thematic analysis of free text questions related to barriers to programmatic establishment or expansion of psychosocial services was performed by two team members until consensus was reached. Results Sixty-eight programs (89%) responded to the survey. Forty-eight programs (70%) indicated offering psychosocial services; however, a majority (73%) of programs reported not directly billing for those services. At program enrollment, mental health was assessed in 94% of programs of which 92% repeated the assessment at discharge. Depression was assessed with the 9-item Patient Health Questionnaire by a majority (75%) of programs. Psychosocial services included individual counseling (59%), counseling referrals (49%), and educational classes (29%). Directors reported lack of internal resources (92%) and patient beliefs (45%) as the top barriers to including or expanding psychosocial services at their facilities. Conclusions Cardiac rehabilitation programs routinely assess mental health but lack the resources to establish or expand psychosocial services. Interventions aimed at improving patient education and reducing stigma of mental health are important public health opportunities.